Choleduodenal fistula with gastric outlet obstruction. (6th April 2016) - Dong, Matthew; Guerron, Alfredo Daniel; Morris-Stiff, Gareth; Chalikonda, Sricharan
Abstract : Bouveret's syndrome, cholecystoduodenal fistula with gastric outlet obstruction secondary to an impacted gallstone, is a rare but serious complication of cholelithiasis. We report the case of a 69-year-old woman who presented with epigastric pain and vomiting in whom cross-sectional imaging revealed a duodenal mass with cholecystoduodenal fistula and pneumobilia. Endoscopic evaluation identified a large gallstone obstructing the pyloric channel. She underwent laparotomy and stone extraction with pyloroplasty, had an unremarkable recovery. She was asymptomatic at 15 months follow-up.